Papillary and sclerosing lesions of the breast detected and biopsied by MRI: Clinical management, upgrade rate, and association with apocrine metaplasia. Issue 3 (3rd April 2019) - Ring, Natalie Y.; diFlorio‐Alexander, Roberta M.; Bond, Jesse S.; Rosenkranz, Kari M.; Cervantes, Eduardo; Sohn, Jae Ho; Marotti, Jonathan D.
Abstract: Benign papillary and sclerosing lesions of the breast (intraductal papillomas, complex sclerosing lesions, radial scars) are considered high‐risk lesions due to the potential for upgrade to carcinoma on subsequent surgical excision. Optimal clinical management of such lesions remains unclear due to variable reported upgrade rates. Apocrine metaplasia is a common finding in breast tissue and its role in MRI enhancing lesions is increasingly being recognized. The purpose of this study was to investigate the MRI features of papillary and sclerosing lesions of the breast, evaluate the clinical management and upgrade rate of such lesions, and examine the contribution of apocrine metaplasia to the imaging findings. A 13‐year retrospective review of MRI‐guided biopsies identified 70 MRI‐detected and ‐biopsied papillary and sclerosing lesions. Sixteen lesions without atypia underwent surgical excision; only one case (6%) was upgraded to pleomorphic lobular carcinoma in situ. The majority (64%) of biopsies contained apocrine metaplasia either within or adjacent to the targeted lesion. We found that half of MRI‐detected lesions had T2 hyperintense foci (2‐5 mm) or masses (>5 mm) adjacent to the lesion. Histologic correlation showed apocrine cysts were likely responsible for this imaging finding in 56% of these cases.